Author Reply: Coregulation is a State of a Temporal Interpersonal Emotion System. (April 2013) - Butler, Emily A.; Randall, Ashley K.
People in an emotional exchange form a temporal interpersonal emotion system (TIES), in which their emotions are interconnected over time (Butler, 2011). These systems can be in various states, defined by the pattern of emotional interconnections. We have defined coregulation as one such state involving coupled dampened oscillations between partners' emotions that converge on a stable level. Coregulation could be distinguished from other states, such as stress buffering, by comparing statistical models that represent the theoretical distinctions between states. Optimal data for such modeling includes assessments of both partners' emotions over time and a contrast between securely attached partners, strangers, and being alone. Research of this sort is needed to uncover the mechanisms by which emotional interdependence promotes well-being.